Efeitos da cirurgia bariátrica sobre a qualidade do sono e os sintomas depressivos e da Síndrome do Comer Noturno - Gomes, Thisciane Ferreira Pinto (2017)
Obesity is commonly associated with depressive symptoms, disturbed sleep and changes in eating pattern, as observed in patients with the Night Eating Syndrome (NES). However, the impact of bariatric surgery (BS) on these conditions has been insufficiently investigated. This thesis seeks to improve current knowledge in this area and comprises three studies. The first study is a critical review of the existing literature on the treatment of NES. A systematic search was performed in PubMed for original clincial studies investigating pharmacological and/or non-pharmacological treatment modalities, from 1955 to 2015. Only 17articles met the selection criteria, highlighting the need for more well-controlled randomized clinical trials. Promising results were reported with the use of serotonergic agents, psychological interventions, and chronobiologic interventions, which deserve further investigation. The second study evaluated the effects of BS on night eating and depressive symptoms in 60 consecutive patients undergoing BS at the Hospital Geral Dr. César Cals (HGCC)in Fortaleza, Brazil. Presence and severity of the NES were evaluated by the night eating questionnaire (NEQ), and a score ≥25 was considered positive for NES. Depressive symptoms were assessed by the Beck Depression Inventory – Short Form (BDI), and a score>4 was indicative of depressive symptoms. A postoperative improvement in the BDI scores (9.77±7.01 vs 4.70±4.60, p=0.001) as well as a trend for an increase in overall NEQ scores (14.18±7.69 vs 12.32±7.66, p=0.05) were observed. Patients with preoperative depressive symptoms showed a greater reduction in NEQ scores compared with those without these symptoms (16.03±7.73 vs 12.80±7.76,respectively; p=0.01), raising the possibility of a causal relationship. In the third study, the course of excessive daytime sleepiness (EDS) and sleep impairment was investigated in 60 patients following BS, at the HGCC. Subjective sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI) and a score>5 indicated poor quality sleep. Daytime sleepiness was evaluated by the Epworth Sleepiness Scale (ESS)and a score ≥10 indicated EDS. The Berlin questionnaire was used to measure the risk for obstructive sleep apnea (OSA). The BDI analyzed the presence and severity of depressive symptoms. Results demonstrated that BS improves PSQI (6.4±3.8 vs 4.1±2.8; p<0.001) and ESS scores (8.1±4.7 vs6.0±3.3, p<0.001), and the risk for OSA [41 (68.3%) vs3 (5%); p<0.001]. Twelve of the 18 participants with EDS normalized their BDI score after BS and in these subjects there was a significant improvement in depressive symptoms (12.0±9.0vs5.5±5.0, p=0.041). In contrast, the six cases with persistent EDS did not significantly improve their depressive symptoms (5.5±5.0 vs3.2±3.1, p=0.416). In conclusion, BS improves sleep quality and EDS and decreases the risk for OSA. Lack of improvement in EDS after BS may be associated with persistence of depressive symptoms.